The role of undergraduate teaching, learning and a national prescribing safety assessment in preparation for practical prescribing: UK medical students' perspective. Issue 10 (1st August 2019) - Kennedy, Maria B.; Haq, Inam; Ferns, Gordon; Williams, Sian E.; Okorie, Michael
Abstract : Aims: To investigate medical students' perspectives on the influence of their undergraduate course and the UK prescribing safety assessment (PSA) on the acquisition of practical prescribing skills. Methods: An online questionnaire comprising multiple choice and open‐ended questions was available to UK medical students in years 3, 4 and 5. Descriptive statistics and thematic analysis were completed. Results: In total, 1023 medical students from 25 UK medical schools responded: 22% (3rd year), 37% (4th year) and 41% (final year). A minority of medical students believed that their medical course prepared them sufficiently for practical prescribing (36.4%, n = 372, 95% confidence interval [CI] = 32–41%), 52.6%, of students thought that practical prescribing should be introduced into the curriculum earlier ( n = 538, CI = 48–57%), and 73.7% reported that a more consistent approach to the teaching and learning of practical prescribing might be beneficial ( n = 754, CI = 71–77%). An awareness of the national PSA was high (86.5%, n = 885), particularly amongst final year students (98.3%, n = 413, CI = 97–100%); 67.4% of all students ( n = 690, CI = 64–71%) and 72.1% ( n = 303) of final year students perceived that the PSA will improve or had improved their practical prescribing skills. Conclusions: The majority of medical students perceive that their undergraduate course does not adequately prepare them for practical prescribing. Many believe that there is some merit in introducing practical prescribing teaching earlier in the curriculum and medical schools adopting a more consistent approach. Among medical students, the PSA is thought to have a positive influence on prescribing skills learning. These data might be useful in developing a programme of study dedicated to practical prescribing.